PREVALÊNCIA DE CETOSE EM VACAS DE CORTE - MARINHO MENDONÇA GUIMARÃES , BRUNO; CARVALHO DE SOUZA , RAFAHEL; MAGALHÃES , HERGOS LEANDRO; M. PEREIRA , HUGO; MACHADO SATURNINO , BRUNO (Sinapse Múltipla, 2019)